2022
DOI: 10.1111/epi.17346
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing seizure clusters in the community: The path to uniformity and individualization in nomenclature and definition

Abstract: Seizure emergencies experienced by patients with epilepsy include status epilepticus and seizure clusters. Although an accepted definition of status epilepticus exists, no clear consensus definition of seizure clusters has emerged; this is further complicated by the appearance in the literature of various empirically based definitions that have been developed for clinical trial study designs. In general, patients with intractable epilepsy have been shown to have a significant risk for acute episodes of increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…See Haut and Nabbout, Recognizing Seizure Clusters in the Community: The Path to Uniformity and Individualization in Nomenclature and Definition for more details regarding the clinical implications of seizure clusters. 57 A number of practical barriers to identifying patients at risk for seizure clusters exist. There is no clear consensus on the definition of a seizure cluster, which complicates identification in the limited time that clinicians have for patient consultations.…”
Section: Identifying Patients At Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…See Haut and Nabbout, Recognizing Seizure Clusters in the Community: The Path to Uniformity and Individualization in Nomenclature and Definition for more details regarding the clinical implications of seizure clusters. 57 A number of practical barriers to identifying patients at risk for seizure clusters exist. There is no clear consensus on the definition of a seizure cluster, which complicates identification in the limited time that clinicians have for patient consultations.…”
Section: Identifying Patients At Riskmentioning
confidence: 99%
“…Patients who experience seizure clusters commonly have refractory epilepsy and higher rates of hospitalization, 1,2 leading to greater health care costs and demands on health care resources. See Haut and Nabbout, Recognizing Seizure Clusters in the Community: The Path to Uniformity and Individualization in Nomenclature and Definition for more details regarding the clinical implications of seizure clusters 57 …”
Section: Impact: Clinical Perspectivementioning
confidence: 99%
“…And in case of no recovery in-between seizures, it may progress into status epilepticus, which becomes more critical and may lead to injury or death [ 8 ]. It has been reported that the prevalence of seizure clusters in outpatient and inpatient studies of patients having epilepsy is 13%-76% and 18%-61%, respectively [ 9 , 10 ]. It has been reported that patients having a history of seizure clusters have 2.5 times more risk for sudden unexplained death in epilepsy (SUDEP).…”
Section: Introductionmentioning
confidence: 99%
“…Ideal rescue therapies should be easy and safe to administer, be effective at small doses (with a large therapeutic index), and exhibit rapid onset of action that can be sustained for several hours. 5 Three rescue therapies are approved by the US Food and Drug Administration (FDA) for the acute treatment of intermittent, stereotypic episodes of frequent seizure activity (i.e., seizure clusters, acute repetitive seizures) that are distinct from the usual seizure pattern in patients with epilepsy (Table 1) [6][7][8] (please see Haut and Nabbout, Recognizing Seizure Clusters in the Community: The Path to Uniformity and Individualization in Nomenclature and Definition 9 for further discussion on seizure cluster definitions in this issue). Diazepam rectal gel (Diastat) was approved for patients ≥2 years of age in 1997.…”
Section: Introductionmentioning
confidence: 99%